The Role of Service Management in Enhancing the Competitiveness of PT. Telkom Indonesia, Tbk - Mifthakhul Fauzi Minarso; Muhammad Farrel Ardyanto; Intan Natalia; Mohamad Zein Saleh (PT Maju Malaqbi Makkarana, 2024)
This research aims to analyze the role of service management in increasing the competitiveness of PT. Telkom Indonesia, Tbk in the competitive telecommunications industry. Using a qualitative approach based on a literature review, this research explores various strategies, such as digitalization of services, technological innovation, and improving the quality of customer service. The research results show that PT Telkom has succeeded in increasing its competitiveness through implementing management strategies, including developing technological infrastructure, big data-based data analysis, and service diversification. Factors such as superior customer experience, partnership strategy and innovation culture also play an important role in strengthening the company's position in the domestic market and opening up global expansion opportunities. In conclusion, the service management strategy implemented not only increases customer satisfaction but also supports digital transformation in Indonesia.